Defect-free ultrathin continuous MOF (Metal Organic Framework) film as well as preparation method and application thereof

By synthesizing defect-free ultra-thin continuous MOF membranes on polyacrylonitrile ultrafiltration membranes, the problems of membrane pollution, flux attenuation and high-concentration pollutant treatment in existing membrane separation technologies are solved, efficient separation and degradation of organic dyes in water are achieved, photocatalytic activity is improved, and effective coupling between membrane separation and photocatalytic technology is achieved.

CN119588181APending Publication Date: 2025-03-11TIAN JIN GONG YE DA XUE SHAO XING KE QIAO YAN JIU YUAN
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411875523.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing membrane separation technology has problems in wastewater treatment, flux attenuation and high-concentration pollutant treatment, and traditional powdered photocatalysts will block membrane pores and affect flux.

Method used

The polyacrylonitrile ultrafiltration membrane modified with amidoxime is used as a support. Through strong interaction and solid-supporting Fe3+, it combines with organic ligands to form a defect-free ultra-thin continuous MOF membrane, achieving efficient separation and degradation of organic dyes in water.

Benefits of technology

It realizes precise regulation of membrane flux and organic pollutant interception rate, improves photocatalytic activity, can effectively oxidize and degrade organic pollutants, solves the problems of membrane pollution and flux attenuation, and realizes the effective coupling between membrane separation and photocatalytic technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588181A_ABST
    Figure CN119588181A_ABST
Patent Text Reader

Abstract

The invention relates to a defect-free ultrathin continuous MOF (Metal Organic Framework) film as well as a preparation method and application thereof. The MOF membrane is synthesized by taking an amidoxime functionalized commercial polyacrylonitrile ultrafiltration membrane as a support body through a diffusion method, and the thickness of the MOF membrane is 22 nm to 1.36 microns. The preparation method comprises the following steps: firstly, respectively preparing aqueous solutions of Fe < 3 + > salt and organic ligands, then respectively placing the aqueous solutions on two sides of a support body, and synthesizing the defect-free ultrathin continuous MOF membrane at room temperature by utilizing a pair diffusion method. Compared with the prior art, the thickness of the defect-free ultrathin continuous MOF membrane is controllable, the minimum thickness can reach 22 nm, the membrane flux and the rejection rate of organic pollutants can be regulated and controlled, the defect-free ultrathin continuous MOF membrane has photocatalytic degradation performance, organic pollutants can be treated through membrane separation and photocatalytic coupling technologies, and the defect-free ultrathin continuous MOF membrane has great application value in the field of wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wastewater treatment membranes, and in particular relates to a defect-free ultra-thin continuous MOF membrane, a preparation method and an application thereof. Background Art

[0002] With the acceleration of industrialization and the increasing frequency of human activities, pollutants in the water environment are increasing. Among them, organic pollutants such as organic dyes and antibiotics pose a serious threat to the ecological environment and human health. Membrane separation technology can remove pollutants in wastewater through the interception of membrane pores, and has attracted much attention in the field of wastewater treatment. However, there are many problems in the practical application of this technology, such as membrane fouling will reduce the service life of the membrane; the membrane flux continues to decay with the use time, resulting in a decrease in treatment efficiency; while pursuing low pore size to improve the interception effect, it is difficult to maintain high flux and achieve an ideal balance of treatment efficiency. Importantly, although membrane separation technology can intercept pollutants, the concentrated high-concentration pollutants still need further treatment, which also limits its large-scale application in wastewater treatment.

[0003] In order to overcome the limitations of membrane separation technology when applied alone, coupling photocatalysis technology with membrane separation technology is considered to be a very promising solution. As a green and friendly environmental purification technology, photocatalysis can use solar energy to produce strong oxidizing species to efficiently degrade organic pollutants. However, when traditional powdered photocatalysts are loaded on the membrane, their pores will be blocked, seriously affecting the membrane flux. In recent years, metal organic frameworks (MOFs), as a porous crystalline material hybridized by metals and organic ligands, have the characteristics and advantages of both traditional semiconductors and molecular catalysts, and have become one of the research hotspots of emerging photocatalysts. More importantly, MOF materials have the characteristics of adjustable pore size and morphological size. Defect-free continuous MOF films synthesized on organic supports are widely used in the field of gas separation. Therefore, synthesizing continuous MOF films on the surface of separation membranes is expected to obtain ideal materials with both separation and catalytic properties in the field of wastewater treatment.

[0004] At present, MOF films synthesized on organic supports are mainly used in the field of separation, and research on the photocatalytic degradation of pollutants by MOF films is still underdeveloped. In addition, the thickness of MOF films synthesized on the surface of organic supports is usually large (>50 nm), which not only reduces the membrane flux, but also affects the photocatalytic activity of MOF. Due to the low overlap of MOF frontier orbitals, it is impossible to drive charge separation through continuous valence band / conduction band energy levels, and its photogenerated carrier migration efficiency is low. Constructing nanoscale ultra-thin MOF sheets can not only reduce the carrier bulk-surface transmission distance, but also expose active sites to promote surface reactions, thereby improving photocatalytic activity. In particular, continuous ultra-thin MOF films are expected to overcome the problems of easy aggregation, light scattering and low stability of MOF sheets, and further improve their photocatalytic degradation efficiency. Therefore, constructing a defect-free ultra-thin continuous MOF film with controllable thickness on the surface of the separation membrane is expected to obtain a composite membrane material with both membrane separation and photocatalytic degradation activity, which has great application prospects in the field of wastewater treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a defect-free ultra-thin continuous MOF membrane, a preparation method and application thereof, so as to achieve efficient separation and degradation of organic dyes in water.

[0006] To achieve the above objectives, the present invention adopts the following technical solutions.

[0007] A defect-free ultrathin continuous MOF membrane comprises a support and a MOF layer arranged on the surface of the support; the support is an amidoxime-modified polyacrylonitrile ultrafiltration membrane, and the MOF membrane layer has a thickness of 22 nm-1.39 μm.

[0008] The support is prepared by: 1) Soak the polyacrylonitrile ultrafiltration membrane in distilled water for 2 h, then dry it at 25°C for later use; 2) Place the polyacrylonitrile ultrafiltration membrane in an aqueous solution of hydroxylamine hydrochloride and sodium hydroxide, with the concentration of hydroxylamine hydrochloride being 50-60 g / L and the concentration of sodium hydroxide being 40-52 g / L. React at 60-80°C for 0.5-1 h, take out and wash with distilled water, and dry at 25°C to obtain the amidoxime-modified polyacrylonitrile ultrafiltration membrane.

[0009] A defect-free ultra-thin continuous MOF film, prepared by: Prepare Fe 3+ Salt solution and aqueous solution of organic ligand, Fe 3+ The concentration of the salt solution is 35-60 g / L, and the concentration of the organic ligand solution is 15-30 g / L; then Fe 3+ The salt solution and the organic ligand aqueous solution are placed on both sides of the support, and the time is 2 min-24 h to obtain a defect-free ultra-thin continuous MOF film.

[0010] The Fe 3+ The salt is preferably ferric chloride hexahydrate or ferric nitrate nonahydrate.

[0011] The organic ligand is preferably fumaric acid or terephthalic acid.

[0012] The defect-free ultra-thin continuous MOF membrane is used in the field of printing and dyeing wastewater treatment.

[0013] Principle of the invention: The present invention adopts amidoximated polyacrylonitrile ultrafiltration membrane as a support, and utilizes amidoxim groups on the support to react with Fe 3+ The strong interaction between Fe 3+ The organic ligands on the other side of the support can diffuse slowly through the pores and interact with Fe 3+ Combined, a defect-free ultrathin continuous MOF film was obtained.

[0014] Compared with the existing MOF membrane, the beneficial effects of the present invention are: (1) The defect-free ultra-thin continuous MOF membrane provided by the present invention has a MOF layer with controllable thickness. The thickness of the MOF layer can be as low as 22±6 nm and as high as 1.36±0.1 μm, which can achieve precise control of membrane flux and organic pollutant retention rate.

[0015] (2) The defect-free ultra-thin continuous MOF film provided by the present invention has high photocatalytic activity and can use sunlight to activate O2 or H2O2 to generate active species and effectively oxidize and degrade organic pollutants. On the one hand, the ultra-thin MOF layer can reduce the migration distance of photogenerated carriers from the interior to the surface, thereby promoting the separation of photogenerated charges and photodegradation efficiency. The defect-free ultra-thin MOF film provided by the present invention has a minimum thickness of 22±6 nm, which is lower than the MOF layer synthesized on the surface of most organic supports, and therefore exhibits high photocatalytic activity. On the other hand, the amidoxime group and Fe 3+ The strong coordination effect of the amidoxime group will break the symmetry of the electronic structure of MOF and induce charge redistribution, thereby enhancing the adsorption and activation of O2 and H2O2, and further improving the photocatalytic activity. In addition, the amidoxime group can also enhance the absorption performance of MOF in the visible light region through the charge transfer effect (LMCT) from the ligand to the metal center, broadening its spectral response range to 800nm, providing conditions for the effective use of sunlight to treat wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Attached Figure 1 Schematic diagram of preparing MOF membrane by diffusion method of the present invention Attached Figure 2 Schematic diagram of the conventional method for preparing MOF membrane Attached Figure 3 The surface scanning electron microscope image of Example 1 is Attached Figure 4 This is a cross-sectional scanning electron microscope image of Example 1. Attached Figure 5 This is a cross-sectional transmission electron microscope image of Example 1. Attached Figure 6 This is a surface scanning electron microscope image of Example 4. Attached Figure 7 This is a cross-sectional scanning electron microscope image of Example 4. Attached Figure 8 Surface scanning electron microscope image of Comparative Example 1 Attached Fig. 9 Surface scanning electron microscope image of Comparative Example 2 Attached Fig.10 UV-visible absorption spectra of polyacrylonitrile ultrafiltration membrane and MOF powder in Examples 1-4 Attached Fig.11 The water flux of Example 1, Example 4 and polyacrylonitrile ultrafiltration membrane Attached Fig.12 The retention rates of Example 1, Example 4 and polyacrylonitrile ultrafiltration membrane for rhodamine B and methylene blue dye are Attached Fig.13 The degradation effect of Examples 1-4 and polyacrylonitrile ultrafiltration membrane on methylene blue dye Attached Fig.14 is the rate constant per unit mass of MOF membrane when degrading methylene blue in Examples 1-4 and Comparative Example 1 DETAILED DESCRIPTION

[0017] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0018] The invention discloses a defect-free ultrathin continuous MOF membrane, comprising a support and a MOF layer arranged on the surface of the support; the support is an amidoxime-modified polyacrylonitrile ultrafiltration membrane, and the MOF membrane layer has a thickness of 22 nm-1.39 μm.

[0019] The support is prepared by: 1) Soak the polyacrylonitrile ultrafiltration membrane in distilled water for 2 h, then dry it at 25°C for later use; 2) Place the polyacrylonitrile ultrafiltration membrane in an aqueous solution of hydroxylamine hydrochloride and sodium hydroxide, with the concentration of hydroxylamine hydrochloride being 50-60 g / L and the concentration of sodium hydroxide being 40-52 g / L. React at 60-80°C for 0.5-1 h, take out and wash with distilled water, and dry at 25°C to obtain the amidoxime-modified polyacrylonitrile ultrafiltration membrane.

[0020] A defect-free ultra-thin continuous MOF film, prepared by: Prepare Fe 3+ Salt solution and aqueous solution of organic ligand, Fe 3+ The concentration of the salt solution is 35-60 g / L, and the concentration of the organic ligand solution is 15-30 g / L; then Fe 3+ The salt solution and the organic ligand aqueous solution are placed on both sides of the support, and the time is 2 min-24 h to obtain a defect-free ultra-thin continuous MOF film.

[0021] The Fe 3+ The salt is preferably ferric chloride hexahydrate or ferric nitrate nonahydrate.

[0022] The organic ligand is preferably fumaric acid or terephthalic acid.

[0023] Example 1 Prepare ferric chloride hexahydrate and fumaric acid solution respectively, the concentration of ferric chloride hexahydrate solution is 17.5 g / L, and the concentration of fumaric acid solution is 7.5 g / L; then 3+ The salt solution and the organic ligand aqueous solution were placed on both sides of the support and the time was 2 min to obtain a defect-free ultra-thin continuous MOF film with a MOF layer thickness of 22±6 nm.

[0024] Example 2 Prepare ferric chloride hexahydrate and fumaric acid solution respectively, the concentration of ferric chloride hexahydrate solution is 35 g / L, and the concentration of fumaric acid solution is 15 g / L; then 3+ The salt solution and the organic ligand aqueous solution were placed on both sides of the support and the time was 30 min to obtain a defect-free ultra-thin continuous MOF film with a MOF layer thickness of 317±2 nm.

[0025] Example 3 Prepare ferric chloride hexahydrate and fumaric acid solution respectively, the concentration of ferric chloride hexahydrate solution is 35 g / L, and the concentration of fumaric acid solution is 15 g / L; then 3+ The salt solution and the organic ligand aqueous solution were placed on both sides of the support and the time was 1 h to obtain a defect-free ultra-thin continuous MOF film with a MOF layer thickness of 637±4 nm. Example

[0026] Prepare ferric chloride hexahydrate and fumaric acid solution respectively, the concentration of ferric chloride hexahydrate solution is 35 g / L, and the concentration of fumaric acid solution is 15 g / L; then 3+ The salt solution and the organic ligand aqueous solution were placed on both sides of the support and the time was set for 24 h to obtain a defect-free ultra-thin continuous MOF film with a MOF layer thickness of 1.39±0.1 μm.

[0027] Comparative Example 1 0.875 g of ferric chloride hexahydrate and 0.377 g of fumaric acid were added to 50 mL of water, and then the support was added to the solution and allowed to stand at 25°C for 24 h to obtain a MOF membrane prepared by a conventional method.

[0028] Comparative Example 2 1) Soak the polyacrylonitrile ultrafiltration membrane in distilled water for 2 h to remove surface impurities, and then dry it at 25°C for later use; 2) The polyacrylonitrile ultrafiltration membrane was placed in water containing 40 g / L sodium hydroxide, reacted at 60°C for 1 h, taken out and washed with distilled water, and dried at 25°C to obtain a carboxyl-modified polyacrylonitrile ultrafiltration membrane.

[0029] 3) Prepare ferric chloride hexahydrate and fumaric acid solutions respectively, the concentration of ferric chloride hexahydrate solution is 35 g / L, and the concentration of fumaric acid solution is 15 g / L. Then fix the carboxyl-modified polyacrylonitrile ultrafiltration membrane in the center of two diffusion cells, pour the ferric chloride hexahydrate solution and fumaric acid solution into the two diffusion cells respectively, and time for 24 hours to obtain a film with MOF grown on the surface of the carboxyl-modified polyacrylonitrile ultrafiltration membrane.

[0030] The embodiments 1-4 and comparative example 2 of the present invention all adopt the Figure 1 The diffusion method shown in FIG. Figure 2 Prepared by the conventional method shown.

[0031] As attached Figure 3 As shown, a defect-free continuous MOF film was observed on the surface of Example 1. Figure 4 And attached Figure 5 It further shows that the thickness of the MOF layer is 22±6 nm. Figure 6 It shows that the surface of Example 4 still presents a defect-free and continuous MOF film. Figure 7 The thickness of the MOF layer increased to 1.39±0.1μm. This indicates that the thickness of the MOF layer is positively correlated with the concentration of reactants and the reaction time. Figure 8 It can be seen that only discontinuous blocky MOF particles are observed on the surface of Comparative Example 1, indicating that conventional in-situ growth methods cannot grow defect-free MOF films on the surface of the support. Fig. 9 As shown in Figure 2, only disordered strip MOF can be observed on the surface of Comparative Example 2, indicating that it is impossible to synthesize a defect-free continuous MOF film on the surface of the polyacrylonitrile ultrafiltration membrane containing carboxyl groups. This may be due to the 3+ Therefore, the amidoxime groups on the surface of the support and the diffusion growth method are necessary conditions for synthesizing defect-free continuous ultra-thin MOF films, and the thickness of the MOF layer can be controlled by controlling the concentration of reactants and reaction time.

[0032] Attached Fig.10 It shows that polyacrylonitrile ultrafiltration membrane only absorbs in the ultraviolet region. 3+ The MOF powder formed by fumaric acid has a narrow absorption range in the visible light region, while Examples 1-4 described in the present invention all show obvious absorption bands in the range of 200-800 nm, which is attributed to the amidoxime group and Fe 3+ The strong absorption bands of Examples 1-4 described in the present invention in the visible light region provide conditions for efficiently utilizing sunlight to treat wastewater.

[0033] Attached Fig.11 It is shown that the membrane flux of Examples 1-4 described in the present invention decreases with the increase of MOF membrane thickness. The pressure difference during the flux test is set to 0.5 MPa and the dye concentration is 0.15 g / L. The flux of Example 1 is close to that of the polyacrylonitrile ultrafiltration membrane, indicating that when the MOF membrane thickness is very low, the MOF layer has almost no effect on the membrane flux. On the contrary, the attached Fig.12 It shows that the MOF membrane of the present invention can increase the retention rate of rhodamine B and methylene blue dyes, and the dye retention rate increases significantly with the increase of the thickness of the MOF layer. The retention rate of methylene blue in Example 4 can reach 80%. These results show that by regulating the thickness of the MOF layer on the support, the membrane flux and the retention rate of organic pollutants can be regulated, so that it can be applied to different wastewater treatment occasions, enriching the practical application range of MOF membranes in the field of wastewater treatment.

[0034] The photocatalytic activity of the embodiment of the present invention was investigated by selecting 0.02mmol / L methylene blue dye with an initial pH of 6.0 as the target pollutant. The specific method is as follows: the embodiment is placed in an aqueous solution of methylene blue, and a photodegradation reaction is carried out under visible light irradiation and the presence of H2O2, with visible light λ >400 nm and H2O2 concentration of 5 mmol / L. The degradation rate is calculated based on the change in dye concentration, and the photocatalytic performance of the unit mass of the MOF film is compared by the kinetic reaction rate. Fig.13 It can be seen that the polyacrylonitrile ultrafiltration membrane has no photocatalytic activity, while Examples 1-4 described in the present invention all show high photocatalytic activity, and the degradation rate of the dye within 20 min is close to 100%. Fig.14 It shows that the reaction rate constant per unit mass of the MOF membrane of Examples 1-4 described in the present invention reaches 12.2-53.3 min -1 g -1 , which is much higher than the value of 5.4min corresponding to Comparative Example 1 -1 g -1, indicating that a defect-free and continuous ultra-thin MOF film is a necessary condition for high catalytic activity. In addition, Example 1 shows a reaction rate constant much higher than that of Examples 2-4, indicating that reducing the thickness of the MOF film can significantly improve its photocatalytic activity.

[0035] These results indicate that the defect-free ultra-thin continuous MOF membrane described in the present invention can not only intercept organic pollutants such as dyes through membrane separation, but also oxidize and degrade organic pollutants through photocatalysis, thereby solving the membrane pollution problem and achieving complete removal of pollutants, and realizing the effective coupling of membrane separation and photocatalytic technology. Moreover, its membrane flux, pollutant interception rate and photocatalytic activity can all be regulated by controlling the thickness of the MOF membrane. It has a wide range of applications in the field of wastewater treatment, and therefore has obvious economic benefits in industrial applications.

Claims

1. A defect-free ultra-thin continuous MOF film, comprising a support and a MOF film layer, characterized in that: The support is a commercial polyacrylonitrile ultrafiltration membrane based on polyester, which is obtained after an amidoxime modification reaction. The MOF layer is synthesized on the surface of the polyacrylonitrile ultrafiltration membrane, and its thickness ranges from 22nm to 1.39 μm.

2. A method for preparing a defect-free ultra-thin continuous MOF film as claimed in claim 1, characterized in that: The steps include: Support preparation 1) Soak the polyacrylonitrile ultrafiltration membrane in distilled water for 2 hours, then dry it at 25°C and set aside. 2) Put the polyacrylonitrile ultrafiltration membrane into an aqueous solution of hydroxylamine hydrochloride and sodium hydroxide, with the concentration of hydroxylamine hydrochloride being 50-60 g / L and the concentration of sodium hydroxide being 40-52 g / L. React at 60-80°C for 0.5-1 hour, take it out, wash it with distilled water, and dry it at 25°C to obtain the amidoxime-modified polyacrylonitrile ultrafiltration membrane.

3. Preparation of a defect-free ultra-thin continuous MOF membrane Prepare Fe 3+ Salt solution and aqueous solution of organic ligand, Fe 3+ The concentration of the salt solution is 35-60 g / L, and the concentration of the organic ligand solution is 15-30 g / L; then Fe 3+ The salt solution and the organic ligand aqueous solution are placed on both sides of the support, and the time is 2 min-24 h to obtain a defect-free ultra-thin continuous MOF film.

4. The method for preparing a defect-free ultra-thin continuous MOF film according to claim 3, characterized in that: The Fe 3+ The salt is preferably ferric chloride hexahydrate or ferric nitrate nonahydrate, and the organic ligand is preferably fumaric acid or terephthalic acid.

Citation Information

Cited By

  • La-MOF-COOH / AO-PAN composite membrane material as well as preparation method and application thereof

    CN120022761A

  • A La-MOF-COOH / AO-PAN composite membrane material, its preparation method and application

    CN120022761B